A new oxo-sterol derivative from the rhizomes of Costus speciosus*. Issue 1 (2nd January 2018) - Kumar, Ashish; Chand, Gopi; Agnihotri, Vijai K.
Abstract: Chemical investigation of the rhizomes of Costus speciosus led to the isolation of a new compound, 22-ketocholesteryl palmitate (1 ) along with four known compounds, 24-methylenecycloartanol (2 ), cycloartanol (3 ), stigmasterol (4 ) and linoleic acid (5 ). The structure of new compound was characterised by extensive 1D-, 2D-NMR and mass spectrometry (GC-MS and HR-ESI-MS) techniques. Abstract :